ANTI-INFLAMMATORY FACTOR DEL-1 PROTECTS FROM ANGIOTENSIN II-DEPENDENT VASCULAR REMODELING AND HYPERTENSION. (June 2018) - Kopaliani, I.; Failer, T.; Neuwith, A.; Hajishengallis, G.; Chavakis, T.; Deussen, A.
Abstract : Objective: Hypertension is the leading cause of mortality worldwide. Critical contributor to pathophysiology of hypertension is vascular remodeling, which is mediated by angiotensin II (ANGII) driven T-cell inflammation and production of interleukin 17 (IL-17). Thus, anti-inflammatory approaches have been proposed as a potential therapeutic strategy. We tested the role of an endogenous anti-inflammatory factor, developmental endothelial locus-1 (Del-1), in prevention of ANGII-induced vascular remodeling and hypertension. Design and method: Mice overexpressing endothelial Del-1 (Del1 Tg) and WT mice which were repetitively injected with soluble Del-1 (50 μg/per injection) were used. Hypertension and vascular remodeling were induced with ANGII infusion using osmotic minipumps (Alzet®) for 4-weeks. Systolic blood pressure (SBP) was measured via tail-cuff method. Aortic remodeling was assessed by quantification of adventitial fibrosis, elastin and medial thickness. Aortic inflammatory cells were quantified with flow cytometry, whereas endothelial dysfunction was assessed using Mulvany myography. Results: After 4-weeks of ANGII infusion, Del-1 Tg mice had lower (P < 0.01) SBP compared to WT littermates. Del-1 Tg mice had less (P < 0.01) aortic medial thickness, less adventitial collagen (P < 0.01) and more elastin (P < 0.01) area compared to WT mice. MMP2 activity was significantly (P < 0.01) less in Del-1 Tg mice than in WT. Endothelium-dependent relaxation of aorta was stronger (P < 0.01) in Del-1 Tg mice than in WT. Del-1 Tg mice had less (P < 0.05) CD45+ leukocytes, TCRβ+ T-cells, as well as CD4+ T-helper and CD8+ T-cytotoxic cells in aorta compared to WT mice. TCRβ+/IL-17+ double positive T-cell count was also less (P < 0.05) in Del-1 Tg than in WT mice. Injections of soluble Del-1 in WT completely protected from ANGII-induced development of hypertension and aortic remodeling. Del-1 injected mice had lower (P < 0.05) SBP compared to vehicle treated mice. Del-1 injections resulted in less aortic medial thickness (P < 0.05) and adventitial collagen area (P < 0.05), as well as lower MMP2 (P < 0.05) activity. Endothelium-dependent relaxation was stronger (P < 0.01) in Del-1 injected mice. Conclusions: Our findings demonstrate that Del-1 protects from ANGII-dependent development of hypertension and vascular remodeling via limitation of inflammation and maintaining of endothelial function. Its proof of efficacy via exogenous injections presents Del-1 as a potential therapeutic agent.